Social differentiation references: A review of Bourdieu and Bateson's thought - Muhammad, Ali Khader Jassim; Salman, Hussein Fadel (Al-Adab Journal, 2022)
The social form is based on a group of small worlds “a group of fields as seen by Bourdieu”, and that each field has its own distinctiveness or interests, and that this specificity, even if it means non-interference or relative independence, it refers to the state of differentiation “social differentiation” whether it is two groups with different cultures. Pattison also sees "the mother of groups belonging to one culture, as the relationship systems of individuals or the group, have a tendency of gradual differentiation "complementary schism". And that the members of each group create sites, and these sites are connected to each other intertwined, and these sites draw for individuals the boundaries that allow them to have a scientific and physical knowledge of the status, so they are able to control their experiences and then their position and make them more respectful to others. It also allows them to produce multiple ways of knowing the social world, in which they exist as a social space, that differ according to the type or specificity of the domain governed by a perceptual and intellectual system. Individuals seek to support their identity, which is represented by preserving everything that makes the group or individual his habitus, and the latter works to distinguish them or to show the state of difference within the sites within the conditions of social existence.